2021
DOI: 10.3390/healthcare10010018
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Third Wave of COVID-19 from the Perspective of the Emergency Department in a Large Regional Hospital—Single Center Observational Study

Abstract: Background: The outbreak of the Coronavirus Disease 2019 (COVID-19) pandemic has caused many significant social and economic changes. The consecutive waves of the epidemic in various countries have had dissimilar courses depending on the methods used to combat it. The aim of this study was to determine the dynamics of the third wave of COVID-19 from the perspective of emergency departments (ED). Methods: This was a retrospective review of medical records from ED. The authors have identified the most frequent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Secondly, there was a need to transport patients to COVID-19-dedicated hospitals or wards, which were also located outside the facility. Furthermore, patients admitted to the hospital required more resources than those discharged home [19].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, there was a need to transport patients to COVID-19-dedicated hospitals or wards, which were also located outside the facility. Furthermore, patients admitted to the hospital required more resources than those discharged home [19].…”
Section: Discussionmentioning
confidence: 99%
“…This is a linear approximation of a nonlinear relationship, which is similar to the approximation a tangent line makes to a curve around the point of tangency, or a plane, that is tangent to a surface-which is our case. We are constructing a plane in three dimensions-one is the active cases, the other is the ratio, and the third dimension is 𝐻 𝑎, 𝑟 in (7). This is a local The model here says that on average, 13.027% of active cases become hospitalized above some number of patients, which depend linearly on the ratio r 60+ .…”
Section: Linear Regression With Pca-hospitalizationsmentioning
confidence: 99%
“…Furthermore, Klosiewicz et al showed dynamics of the third wave of COVID-19 in a Polish single-center study. Therefore, new biomarkers are needed for decision making regarding medical treatment to shorten the duration of hospitalization in emergency departments, such as blood oxygen saturation [7].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noticing that providing medical help to patients in life-threatening conditions was continued regardless of the number of COVID-19 patients. However, the changing profile of admissions and the need for increased sanitary rigor has forced a change in the organization of emergency departments (ED) [2]. Early detection and isolation of patients with COVID-19 was crucial to be able to provide appropriate help to patients with other diseases [3,4].…”
Section: Introductionmentioning
confidence: 99%